Teaching English for Translation and Interpreting: A framework of reference for developing the translator’s bilingual sub-competence - Carrasco Flores, José Andrés (Complutense Journal of English Studies, 2019)
Even though the research on translator training explicitly advocates specific language training catering for translator and interpreter trainees’ needs, only a few, scattered attempts seem to have been made as regards the identification and provision of specific approaches guiding the teaching of such newly appointed branch of Languages for Specific Purposes. Drawing on previous studies on translator training and translation competence, this paper elaborates on the notion of the translator’s bilingual sub-competence and puts forward a framework of reference for teaching English for Translation and Interpreting, which can be used in the materials analysis and development.